Leadership behaviour and satisfaction in young table tennis players - Zerdila, D.; Kordoutis, I.; Rokka, S.; Mavridis, G.; Papadimitriou, A. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The main purpose of this study was to examine the relationship between the perceived and preferred leadership behaviour of young table tennis players and their satisfaction and secondly to investigate possible differences related to gender, competition league and years of practice. The sample consisted of 162 table tennis players (103 boys and 59 girls) from Athens and Northern Greece with a mean age 15.3 ± 1.52. Data was collected through Leadership Scale for Sports, in its two versions (perceived and preferred of athletes) and the Athlete`s Satisfaction Scale. The statistical methods included reliability analysis, correlation analysis, t-test and one-way analysis of variance. The results indicated that the most perceived and preferred leadership behaviours were training and instructions and positive feedback and the least was autographic behaviour. Further results showed that, athletes` satisfaction had significant correlation with all four leadership behaviour dimensions in the perceived and the preferred version, while the autographic behaviour had a significant negative effect on the player`s satisfaction. Additionally, the girls seem to feel more satisfied than boys with the leadership behaviour of their coaches while competition league and years of practice didn`t influence the satisfaction the players felt from both Leadership and personal outcome.